Evaluation of an Intensive Program for Children With Co-occurring Medical and Emotional Disorders. (October 2022) - Girardet, Rebecca G.; Shellman, Alison B.; Llorens, Ashlie; Nguyen, Linh; Ellsworth, Misti; Rennie, Kimberly; Ha, Carolyn
The study objective was to assess clinical outcomes and cost avoidance of an intensive day treatment program for children with co-occurring chronic medical disease and emotional problems. Intensive day treatment programs for this population are uncommon, and their effectiveness has not been previously reported. A total of 175 children were enrolled during the 3-year study period. Children had more than 30 medical diagnoses including chronic pain, dysautonomia, neurologic disorders, and diabetes. Complete utilization data were available for 118 patients, and demonstrated decreased hospitalizations and increased behavioral health visits during the 12 months post program compared with 12 months prior. Private insurance and female sex were associated with reduced utilization costs after program participation. Estimated avoided cost for the 118 children was 1 111 485. Patients reported significant improvements in somatic symptoms, sleep problems, inattention, depression, anger, and anxiety. Limited data indicated improvements in school attendance. Additional research addressing other outcomes, such as school-related symptoms, would be helpful.